Virtual work system and operational efficiency in organizations - Opiah Ayaokpo Alex; Bio Basuo Kuroakegha (Journal of Commerce, Management, and Tourism Studies, 2026)
The swift paradigm shifts to embracing a virtual work system necessitated by the COVID-19 pandemic have drastically fast-tracked and revolutionized organizational operations. As modern organizations progress in piloting this contemporary route meticulously, there constantly lies the critical need for managers to understand and fathom the significance of the virtual work system on the firms’ operational efficiency. These, however, have presented unprecedented opportunities but have also invariably introduced unique, complex challenges that need to be checkmated. Using the exploratory research design approach and drawing from the Technology Acceptance Model (TAM), this paper reveals the need for practicing a virtual work system and supports that organizational efficiency can be achieved through flexibility, reduction of running cost, minimal work spaces, etc., while leveraging on modern innovations to enhance employees’ work-life balance.